Implementation of Article 25-A of the Constitution of the Islamic Republic of Pakistan in Punjab and KPK: A Critical Analysis of Government’s Memorandum and Shortcomings (Al-Qamar, 2021)
Education is one of the key factors to make a country's socio-economic conditions a better place. Pakistan, a signatory to EFA, UN conventions on education, and several other educational policies, still needs to develop the educational sector concerning free education. One of the significant causes of failure to achieve this goal is a catastrophe in strategically implementing clause Article 25-A mentioned under constitution 1973. What exactly Pakistan needs to do is to present identical policies across provinces through the competent staff for tutoring the same curriculum with the allocation of Budget at 4% of GDP while taking the complete support of bureaucracy and politicians; otherwise to boost up education sector would be considered as a vision only rather than a reality. The study also suggests that local bodies, with the help of NGOs, should take this concern from the primary level to the secondary level, at least around all provinces irrespective of gender, class, and area.
Keywords: Article 25-A; Female Literacy; Free education; Uniform Policy; Schooling; HDIR; GDP